Diagnóstico situacional de tecnologías aplicadas al ordeño en la producción de leche de ganado vacuno en la finca “Santa Teresita” del cantón Oña - Sisalima Peláez, Stefany Madeleyne (2024)
Currently, due to the emergence of technological advances, the dairy industry has experienced significant progress with the arrival of technological tools that have made it possible for the traditional milking system to be replaced by more efficient and current mechanisms that allow automated milking, guaranteeing the quality of the product and the well-being of cattle. Due to this fact, several farms have implemented mechanical and automated systems that not only increase milk production, but also optimize time and labor, which in turn improves product quality, since the automatic cleaning of the systems reduces the presence of bacterial agents. The present research aims to diagnose the technologies applicable to the milking process in the production of cattle milk at the "Santa Teresita" farm in the Oña canton during the period May-August 2024, with the aim of identifying what are the current technologies that the farm is carrying out in the milking process. To this end, a qualitative methodology of a descriptive and exploratory nature was used, which analyzed the current activities of the farm and proceeded to propose technological and operational improvements to optimize the milking process and milk production at the "Santa Teresita" farm in the Oña canton.